Bernard Bolzano’s philosophical conception of education from a modern standpoint - Synytsia, Andrii (Journal of Education Culture and Society, 2021)
Aim. The aim of the article is to analyse Bernard Bolzano’s philosophico-educational approach, given the importance of his pedagogical legacy for further progress in the field of education and training.Methods. The research uses methods of historico-philosophical reconstruction (to determine the foundations and features of Bolzano’s pedagogico-philosophical work), interpretation (to characterise the still relevant ideas of the thinker in the field of education) and critical analysis (to assess the significance of Bolzano’s legacy from the standpoint of modern educational theory and to point out what remained out of the researchers’ attention).Results. The study showed that Bolzano’s pedagogical ideas were not only in demand in the context of European culture of the early XIX century, but also proved relevant today, especially given the need for harmonious personal development, finding sources of intrinsic motivation in students and improving their logical thinking skills, the importance of the spiritual qualities of the teacher and – in general – the assistance of the state in the direction of the progress of education as the most effective means of qualitative change in society.Conclusion. Bernardo Bolzano’s philosophical conception of education was strongly influenced by religion, the ideas of the late Enlightenment and the late Josefinist. This conception was an integral part of his socio-political theory. Bolzano attached great importance to the study of philosophy and the acquisition of logical skills in education. He considered writing textbooks to be one of the cornerstones of the educational process. This made it possible to intensify communication between teachers and students, to gradually involve everyone in education, and thus to promote social progress in general.